Advances in global leadership. Vol. 10 - Osland, Joyce S.; Mendenhall, Mark E., 1956-; Li, Ming, active 2017 (Emerald Publishing Limited, 2017)
Volume 10 of Advances in Global Leadership continues to advance both globalleadership research and practice by bridging and integrating conceptual andpractitioner perspectives to provide a deeper understanding of this rapidlygrowing field of study. This volume contains both innovative foundationalresearch on global leadership processes and new models to advance theoreticalwork. The 'Practitioner's Corner' section of the volume contains lessons fromthree experts with decades of experience in developing global leaders from bothbusiness and non-profits. This volume also provides detailed descriptions ofground-breaking university global leadership development programs. As always,the editors conclude the volume with an overview of the current state of thefield and a summary of the key research needs and directions to guide futurescholarship.- Resumé vydavatel
Obsahuje index.
Keywords: vůdcovství; management; nadnárodní společnosti; leadership; international business enterprises; kolektivní monografie; elektronické knihy; collective monographs; electronic books